A Dynamic Study on the Market Share Growth of Islamic Banks in Indonesia Post Spin-off, Conversion, and Merger Mario - Huzni Mubarok; Sri Mulatsih; Irfan Syauqi Beik (Journal of World Science, 2025)
This research aims to examine the impact of microprudential policies, specifically spin-offs, conversions, and mergers, on Islamic banks in Indonesia, both directly and indirectly through transmission variables, in relation to the growth of the Islamic banking market share. The method used in this study is the dynamic ARDL model, which was chosen for its ability to accommodate data stationarity, cointegration, and short- and long-term relationships. This study utilizes monthly time series data from Bank Umum Syariah (BUS) and Unit Usaha Syariah (UUS) in Indonesia, covering the period from January 2008 to December 2023, resulting in 192 observations for each variable. The data were processed using MS Excel and EViews 10. This research finds that only conversion has a significant direct impact on market share in both the short and long run, while mergers are significant only in the long run, and spin-offs are insignificant in both time frames. As for the transmission variables, DPK and ROA consistently drive market share growth in both the short and long run. NPF is significant only in the long-term simultaneous impact model, where its increase hampers market share growth, whereas FDR is significant only in the short-term simultaneous impact model, where its increase promotes market share. This study incorporates all three microprudential policies—spin-offs, conversions, and mergers—within a single equation model, accompanied by the use of a dynamic model that has not been employed in previous studies. This approach allows for the examination of both short-term and long-term effects.